Remote ischaemic pre-conditioning does not attenuate ischaemic left ventricular dysfunction in humans. - Hoole, S; Khan, SN; White, P; Heck, P; Kharbanda, R; Densem, C; Clarke, S; Shapiro, L; Schofield, P; O'Sullivan, M; Dutka, D (2009)
AIMS: Remote ischaemic pre-conditioning (RIPC) reduces distant tissue ischaemia reperfusion injury. We tested the hypothesis that RIPC would protect the left ventricle (LV) from ischaemic dysfunction and stunning. METHODS AND RESULTS: Forty-two patients with single vessel coronary disease and normal LV function were prospectively recruited. Twenty patients had repeated conductance catheter assessment of LV function during serial coronary occlusions with/without RIPC and a further 22 patients underwent serial dobutamine stress echocardiography and tissue Doppler analysis with/without RIPC. Remote ischaemic pre-conditioning was induced by three 5 min inflations of a blood pressure cuff around the upper arm. RIPC did not diminish the degree of ischaemic LV dysfunction during coronary balloon occlusion (Tau, ms: 59.2 (2.8) vs. 62.8 (2.8), P = 0.15) and there was evidence of cumulative LV dysfunction despite RIPC [ejection fraction (EF), %: 54.3 (5.8) vs. 44.9 (3.7), P = 0.03]. Remote ischaemic pre-conditioning did not improve contractile recovery during reperfusion (EF, %: 51.7 (3.6) vs. 51.5 (5.7), P = 0.88 and Tau, ms: 55.6 (2.8) vs. 56.0 (2.0), P = 0.85). A neutral effect of RIPC on LV function was confirmed by tissue Doppler analysis of ischaemic segments at peak dobutamine (V(s), cm s(-1) control: 8.2 (0.4) vs. RIPC 8.1 (0.4), P = 0.43) and in recovery. CONCLUSION: RIPC does not attenuate ischaemic LV dysfunction in humans.